PENERIMAAN KONSUMEN TERHADAP SELAI RUMPUT LAUT (Kappaphycus alvarezii) - Wonggo, Djuhria (Sam Ratulangi University, 2010)
Seaweed jam can be made by dry seaweed or fresh seaweed.Â Research result indicated that dry seaweed jam and fresh seaweed jam can be accepted by consumer.Â In the tekstur and color perspective, dry seaweed jam and fresh seaweed jam in the good graces (point 4), whereas in smell perspective, both of the jam rather in the good graces (point 3).Â Taste of the dry seaweed jam is in the good graces (point 4) whereas fresh seaweed jam rather in the good graces (point 3) by consumer.